The Development of Multicultural Education Model in West Kalimantan - Kristianus Kristianus (JETL (Journal of Education, Teaching and Learning), 2017)
This study background is from the history of West Kalimantan as an area that has the potential for violent conflict in the name of ethnicity. This potential is supported by the shift of the demographic map, from homogeneous to heterogeneous society. Segregation population continues to occur when the autonomous regions were accompanied by a local election. At the beginning of this year, for example, we were struck increased intolerance. The potential of violent conflict continues to arise in every operation of the democratic party at the local level. To determine the potential of multi-cultural knowledge in students, the authors conducted research on the two schools with different types of contrast. The research was carried out for two months with ethnographic methods. The author conducted in-depth interviews as well in addition to observation and review of the literature. These results indicate that teens from both schools studied generally have a multicultural knowledge is still relatively low, but they want to learn the culture of the ethnic other. Multicultural education in adolescents (students) is influenced by two factors: internal factors (instrumental) and external factors (environmental). The instrumental factors, among others: the teens themselves, teachers, family, and peers, whereas environmental factors, among others, media, and government (policy). Another important finding is that regional autonomy could be access for schools in encouraging alternative education models as a result of their creative efforts into spaces of democracy and pluralism in schools. Relations between the school through the activities of the organization-Students' Union (OSIS) can be a bridge multicultural adolescent relationships in these two schools. The author realizes there are still many shortcomings of this study, for that kind of research still needs to be done